2019
DOI: 10.1111/eea.12866
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between parasitoids and pathogens for biological control of Helicoverpa armigera in chickpea

Abstract: The chickpea pod borer, Helicoverpa armigera H€ ubner (Lepidoptera: Noctuidae), is an important pest of many legume crops, including chickpea, Cicer arietinum L. (Fabaceae). We field-tested the efficacy of two pathogens, Helicoverpa armigera nucleopolyhedrosis virus (HaNPV) and Bacillus thuringiensis Berliner subsp. kurstaki (Btk), both alone and in combination with the parasitoid Habrobracon hebetor Say (Hh) (Hymenoptera: Braconidae), for control of H. armigera larvae in chickpea fields. A randomized complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Similarly, the present investigations for higher yield in chickpea in the studies for management of gram caterpillar on chickpea crop are in agreement to those of Ahmed and Khalique (2012) and Taggar et al (2014) who also reported highest yield of pigeonpea in Bt treated plots over the untreated plots. The present work is in agreement with Allahyari et al (2020) who in their studies for management of H. armigera with Bt formulation also recorded higher yield in Bt treated plots (786.42 kg/ha) over the untreated plots (627.49 kg/ha).…”
Section: Yieldsupporting
confidence: 93%
“…Similarly, the present investigations for higher yield in chickpea in the studies for management of gram caterpillar on chickpea crop are in agreement to those of Ahmed and Khalique (2012) and Taggar et al (2014) who also reported highest yield of pigeonpea in Bt treated plots over the untreated plots. The present work is in agreement with Allahyari et al (2020) who in their studies for management of H. armigera with Bt formulation also recorded higher yield in Bt treated plots (786.42 kg/ha) over the untreated plots (627.49 kg/ha).…”
Section: Yieldsupporting
confidence: 93%
“…Although some notable successes have been recorded [1,2], interactions between two or more natural enemies are not straightforward and the outcome may be counterproductive [3,4]. Interactions can be synergistic-the cumulative efficacy of both species being significantly higher than the efficacy of the two natural enemies when used separately [5]-or additive-when the combined use of both natural enemies is more effective and equal to the added efficacy by each species alone [6]. In other cases, interactions may be equivalent-when the combined impacts of both natural enemies are equal to the more effective of the two species [7].…”
Section: Introductionmentioning
confidence: 99%
“…This eventuality might be delayed or precluded if releases of H. hebetor reduce the survival of resistant genotypes. Allahyari et al (2020b) found evidence of additivity between Btk and H. hebetor in controling H. armigera on chickpea in an earlier field study, which would support their effectiveness in joint application. Thus, even though Btk had some negative effects on H. hebetor under laboratory conditions, and the parasitoid failed to discriminate against hosts treated with low concentrations of Btk , we conclude that these two biocontrol agents are potentially compatible for combined application against H. armigera under field conditions.…”
Section: Discussionmentioning
confidence: 58%
“…The basal container was covered with a second container (15 cm diameter × 13 cm height) ventilated by means of a fine mesh glued to an aperture cut in the bottom (7 cm diameter). Both containers had sloping sides, so that a larva-proof seal was obtained when the larger container was placed upside down over the smaller one ( Allahyari et al 2020b ). The second-instar H. armigera larvae were then left to feed on the Btk -treated chickpea plants for 3 d under the same physical conditions as the insect colony.…”
Section: Methodsmentioning
confidence: 99%